A carbon fiber based CH 4 -CO 2 Reforming catalyst and preparation method thereof
The preparation of carbon fiber-based CH4-CO2 reforming catalysts through electrospinning method solved the problem of inactivation of existing catalysts at high temperatures, achieved high activity and stability of the catalyst, solved the problems of sintering and carbon deposits, and improved the catalyst's performance.
Patent Information
- Application Number
- CN202310049746.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-01
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-02-01
AI Technical Summary
The existing CH4-CO2 reforming catalysts are prone to inactivation due to sintering of active metals and carbon deposits under high temperature conditions, making it difficult to achieve industrial application.
The activated metal-carbon composite nanofibers were prepared by electrospinning, and calcined in an inert atmosphere to obtain a carbon fiber-based CH4-CO2 reforming catalyst. The active metal salt and carbon precursor were mixed by electrospinning to form nanofibers. And calcined under specific conditions to improve the activity and stability of the catalyst.
The catalytic activity and stability of the CH4-CO2 reforming catalyst is improved, the influence of sintering and carbon deposit on the catalyst is reduced, and the anti-sintering performance and electron transfer ability of the catalyst are significantly improved.
Smart Images

Figure BDA0004057325740000071 
Figure BDA0004057325740000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of CH4-CO2 reforming catalysts, in particular to a carbon fiber-based CH4-CO2 reforming catalyst and a preparation method thereof. Background Art
[0002] CH4 and CO2 are two major greenhouse gases and two major carbon sources. CH4 and CO2 can be converted into synthesis gas (CO+H2) by CH4-CO2 reforming reaction. This reaction has extremely high environmental benefits and industrial value for the conversion and utilization of greenhouse gases and the production of clean energy.
[0003] The main reason why CH4-CO2 reforming reaction is difficult to achieve industrialization at present is the deactivation problem of CH4-CO2 reforming catalyst. When conducting CH4-CO2 reforming reaction, metal catalysts such as nickel are often used to catalyze the reforming reaction. However, under high temperature reaction conditions, the activity of CH4-CO2 reforming catalyst decreases or even deactivates due to reasons such as sintering of active metals and carbon deposition. Therefore, it is necessary to design a CH4-CO2 reforming catalyst with good CH4-CO2 reforming catalytic activity and high catalytic activity stability. Summary of the invention
[0004] To this end, the technical problem to be solved by the present invention is to provide a method for preparing a carbon fiber-based CH4-CO2 reforming catalyst. The preparation method can be used to prepare a carbon fiber-based CH4-CO2 reforming catalyst with good catalytic activity and high catalytic stability, so as to solve the problem that the existing CH4-CO2 reforming catalyst is easily deactivated due to active metal sintering and carbon deposition under high temperature conditions.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a carbon fiber-based CH4-CO2 reforming catalyst comprises preparing active metal-carbon composite nanofibers by an electrostatic spinning method, and calcining the active metal-carbon composite nanofibers in an inert atmosphere to obtain a carbon fiber-based CH4-CO2 reforming catalyst.
[0007] The preparation method of the carbon fiber-based CH4-CO2 reforming catalyst specifically comprises the following steps:
[0008] S1: dispersing the active metal salt in an ethanol solution to obtain a mixed dispersion;
[0009] S2: adding a carbon-containing precursor to the mixed dispersion, stirring and mixing until the carbon-containing precursor is completely dispersed and uniformly dispersed, thereby obtaining an electrospinning material;
[0010] S3: preparing active metal-carbon composite nanofibers from the electrospinning material by an electrospinning method;
[0011] S4: placing the active metal-carbon composite nanofibers in a tubular furnace, introducing an inert gas (nitrogen or argon) for calcination, and naturally cooling after the calcination to obtain a carbon fiber-based CH4-CO2 reforming catalyst.
[0012] In the preparation method of the above-mentioned carbon fiber-based CH4-CO2 reforming catalyst, in step S1, the active metal salt is any one of cobalt nitrate, cobalt acetate or cobalt acetylacetonate, or a mixture of two or more thereof; the ethanol solution is a mixture of anhydrous ethanol and water in a volume ratio of 5:5 to 7:3.
[0013] In the preparation method of the above-mentioned carbon fiber-based CH4-CO2 reforming catalyst, in step S1, in the mixed dispersion, the ratio between the mass of the active metal salt and the volume of the ethanol solution is 0.04-0.08 g / mL; if the content of the active metal salt in the mixed dispersion is too low, it may affect the activity of the prepared catalyst, but if the content of the active metal salt is too high, it may cause electrostatic spinning to be unable to proceed or the active metal is prone to agglomeration during electrostatic spinning, resulting in poor dispersion, thereby affecting the catalytic activity of the prepared reforming catalyst.
[0014] In the preparation method of the carbon fiber-based CH4-CO2 reforming catalyst, in step S2, the carbon-containing precursor is any one of polyvinyl alcohol PVA, polyacrylonitrile PAN, polyurethane PU, polyvinyl pyrrolidone PVP or polymethyl methacrylate PMMA, or a mixture of two or more thereof. The carbon nanofibers prepared by electrospinning using the above carbon-containing precursors can effectively inhibit the agglomeration of active metals and thus maintain the integrity of active species, and the prepared CH4-CO2 reforming catalyst can significantly improve the electron transfer performance of the surface of the CH4-CO2 reforming catalyst.
[0015] In the preparation method of the above-mentioned carbon fiber-based CH4-CO2 reforming catalyst, in step S2, the molar ratio of the active metal in the mixed dispersion to the carbon atoms in the carbon-containing precursor is 1:(5-15); using the electrospinning material within this ratio range for electrospinning is beneficial to improving the efficiency of electrospinning, obtaining more ideal active metal-carbon composite nanofibers, and being able to obtain a CH4-CO2 reforming catalyst with good catalytic activity and catalytic stability.
[0016] The preparation method of the above-mentioned carbon fiber-based CH4-CO2 reforming catalyst, in step S3, during the electrospinning process, the electrospinning material is placed in the syringe of the electrospinning equipment, and the injection pump flow rate is 10-15 μL / min; the external voltage is set to 13-19 kV [the structure and performance of the composite nanofibers obtained under the applied voltage in this range are better. If it exceeds this range, the structure and performance of the active metal-carbon composite nanofibers obtained by electrospinning will be significantly reduced], and the receiving distance is 15-20 cm; the active metal-carbon composite nanofibers are received by aluminum foil.
[0017] In the preparation method of the above-mentioned carbon fiber-based CH4-CO2 reforming catalyst, in step S3, the diameter of the active metal-carbon composite nanofibers is 200 to 400 nm; the CH4-CO2 reforming catalyst obtained after calcining the active metal-carbon composite nanofibers within this diameter range has a larger specific surface area, and the active metal is more evenly dispersed on the carbon fiber carrier, so that the CH4-CO2 reforming catalyst exhibits better catalytic activity and catalytic stability.
[0018] In the preparation method of the above-mentioned carbon fiber-based CH4-CO2 reforming catalyst, in step S4, during calcination, the tubular furnace is first heated to the calcination temperature at a heating rate of 5°C / min [if the heating rate is too fast or too slow, it will affect the morphology of the carbon nanofibers, which is not conducive to the formation of a CH4-CO2 reforming catalyst with high catalytic activity and good catalytic stability], and then calcined at the calcination temperature; the calcination temperature is 700-800°C [this calcination temperature is slightly higher than the CH4-CO2 dry reforming reaction temperature, which can ensure that the prepared reforming catalyst has good catalytic stability], and the calcination time is 3-5h. If the calcination time is too short, the metal oxide is not completely generated, affecting the catalytic activity of the obtained catalyst.
[0019] A carbon fiber-based CH4-CO2 reforming catalyst is prepared by using the above-mentioned method for preparing the carbon fiber-based CH4-CO2 reforming catalyst.
[0020] The technical solution of the present invention achieves the following beneficial technical effects:
[0021] 1. The present invention adopts an electrospinning method to prepare a carbon fiber-based CH4-CO2 reforming catalyst in a one-step process. The composite carbon material carrier prepared by the electrospinning method has a large specific surface area and a rich pore structure. The large specific surface area improves the dispersibility of the active metal and provides more active sites for the CH4-CO2 reforming catalyst. The rich void structure has a confinement effect on the active metal to reduce the sintering of the active metal, thereby improving the anti-sintering performance of the CH4-CO2 reforming catalyst. At the same time, it can reduce the influence of carbon deposition on the catalytic activity of the CH4-CO2 reforming catalyst, and further improve the catalytic stability of the CH4-CO2 reforming catalyst.
[0022] 2. The CH4-CO2 reforming catalyst prepared by the present invention has good catalytic activity and catalytic stability. The large specific surface area of the active metal-carbon composite carbon nanofiber can provide abundant metal active sites, and the fiber network composed of the carbon nanofibers with a high aspect ratio can effectively accelerate the electron transfer and the transmission capacity of the reaction gas, thereby effectively improving the catalytic activity and catalytic stability of the CH4-CO2 reforming catalyst. DETAILED DESCRIPTION
[0023] Example 1
[0024] The preparation method of the carbon fiber-based CH4-CO2 reforming catalyst of this embodiment comprises the following steps:
[0025] S1: Dispersing the active metal salt in the ethanol solution, stirring thoroughly until completely dissolved, to obtain a mixed dispersion; in this embodiment, the active metal salt is 0.8 g of cobalt nitrate, and the ethanol solution is prepared by mixing 7 mL of anhydrous ethanol and 3 mL of distilled water;
[0026] S2: Add 0.5 g of carbon-containing precursor polyacrylonitrile PAN powder to the mixed dispersion and continue stirring for 6 h. After mixing, a red gel is obtained as an electrospinning material for later use;
[0027] S3: Loading the electrospinning material into the syringe of the electrospinning device, and preparing the active metal-carbon composite nanofiber membrane by the electrospinning method; during the electrospinning process, setting the external voltage to 15 kV, receiving the active metal-carbon composite nanofiber through the aluminum foil, and forming the active metal-carbon composite nanofiber membrane, the distance between the nozzle and the aluminum foil receiver during receiving is 18 cm; the injection pump flow rate is 10 μL / min;
[0028] S4: placing the active metal-carbon composite nanofibers in a tubular furnace, introducing inert gas argon for calcination; during calcination, setting the heating rate of the tubular furnace to 5°C / min, the calcination temperature to 800°C, and the calcination time to 2h; after calcination, naturally cooling is performed to obtain a carbon fiber-based CH4-CO2 reforming catalyst, recorded as catalyst A.
[0029] Example 2
[0030] The preparation method of the carbon fiber-based CH4-CO2 reforming catalyst of this embodiment comprises the following steps:
[0031] S1: Dispersing the active metal salt in the ethanol solution, stirring thoroughly until completely dissolved, to obtain a mixed dispersion; in this embodiment, the active metal salt is 0.49 g of cobalt acetate, and the ethanol solution is prepared by mixing 7 mL of anhydrous ethanol and 3 mL of distilled water;
[0032] S2: Add 0.5 g of carbon-containing precursor polyacrylonitrile PAN powder to the mixed dispersion and continue stirring for 6 h. After mixing, a red gel is obtained as an electrospinning material for later use;
[0033] S3: Loading the electrospinning material into the syringe of the electrospinning equipment, and preparing active metal-carbon composite nanofibers by electrospinning; during the electrospinning process, setting an external voltage of 15 kV, receiving the active metal-carbon composite nanofibers through the aluminum foil, and forming an active metal-carbon composite nanofiber membrane, the distance between the nozzle and the aluminum foil receiver during receiving is 18 cm; the injection pump flow rate is 10 μL / min; the diameter of the active metal-carbon composite nanofibers is 200-400 nm;
[0034] S4: placing the active metal-carbon composite nanofibers in a tubular furnace, introducing inert gas argon for calcination; during calcination, setting the heating rate of the tubular furnace to 5°C / min, the calcination temperature to 800°C, and the calcination time to 2h; after natural cooling after the calcination, a carbon fiber-based CH4-CO2 reforming catalyst can be obtained, which is recorded as catalyst B.
[0035] Example 3
[0036] The preparation method of the carbon fiber-based CH4-CO2 reforming catalyst of this embodiment comprises the following steps:
[0037] S1: Dispersing the active metal salt in the ethanol solution, stirring thoroughly until completely dissolved, to obtain a mixed dispersion; in this embodiment, the active metal salt is 0.8 g of cobalt nitrate, and the ethanol solution is prepared by mixing 7 mL of anhydrous ethanol and 3 mL of distilled water;
[0038] S2: Add 0.5 g of carbon-containing precursor polyvinyl alcohol (PVA) powder to the mixed dispersion and continue stirring for 6 h. After mixing, a red gel is obtained as an electrospinning material for later use.
[0039] S3: Loading the electrospinning material into the syringe of the electrospinning equipment, and preparing active metal-carbon composite nanofibers by electrospinning; during the electrospinning process, setting an external voltage of 15 kV, receiving the active metal-carbon composite nanofibers through the aluminum foil, and forming an active metal-carbon composite nanofiber membrane, the distance between the nozzle and the aluminum foil receiver during receiving is 18 cm; the injection pump flow rate is 10 μL / min; the diameter of the active metal-carbon composite nanofibers is 200-400 nm;
[0040] S4: placing the active metal-carbon composite nanofibers in a tubular furnace, introducing inert gas argon for calcination; during calcination, setting the heating rate of the tubular furnace to 5°C / min, the calcination temperature to 800°C, and the calcination time to 2h; after calcination, naturally cooling is performed to obtain a carbon fiber-based CH4-CO2 reforming catalyst, recorded as catalyst C.
[0041] By adopting the same method and parameter conditions as in this example, except that polyvinyl alcohol PVA is replaced by polyvinyl pyrrolidone PVP, a carbon fiber-based CH4-CO2 reforming catalyst can be prepared, which is denoted as catalyst C1.
[0042] Example 4
[0043] The preparation method of the carbon fiber-based CH4-CO2 reforming catalyst of this embodiment comprises the following steps:
[0044] S1: Dispersing the active metal salt in the ethanol solution, stirring thoroughly until completely dissolved, to obtain a mixed dispersion; in this embodiment, the active metal salt is 0.8 g of cobalt nitrate, and the ethanol solution is prepared by mixing 7 mL of anhydrous ethanol and 3 mL of distilled water;
[0045] S2: Add 0.5 g of carbon-containing precursor polyacrylonitrile PAN powder to the mixed dispersion and continue stirring for 6 h. After mixing, a red gel is obtained as an electrospinning material for later use;
[0046] S3: Loading the electrospinning material into the syringe of the electrospinning equipment, and preparing active metal-carbon composite nanofibers by electrospinning; during the electrospinning process, setting the applied voltage to 13 kV, receiving the active metal-carbon composite nanofibers through the aluminum foil, and forming an active metal-carbon composite nanofiber membrane, the distance between the nozzle and the aluminum foil receiver during receiving is 18 cm; the injection pump flow rate is 10 μL / min; the diameter of the active metal-carbon composite nanofibers is 200-400 nm;
[0047] S4: placing the active metal-carbon composite nanofibers in a tubular furnace, introducing inert gas argon for calcination; during calcination, setting the heating rate of the tubular furnace to 5°C / min, the calcination temperature to 800°C, and the calcination time to 2h; after natural cooling after the calcination, a carbon fiber-based CH4-CO2 reforming catalyst can be obtained, which is recorded as catalyst D.
[0048] Using the same method and parameter conditions as in this embodiment, only the applied voltage is set to 17 kV and 19 kV, two carbon fiber-based CH4-CO2 reforming catalysts can be prepared, which are respectively denoted as catalyst D1 and catalyst D2.
[0049] The CH4-CO2 reforming catalysts prepared in the above examples were subjected to catalytic tests respectively. Under the same reaction conditions, i.e., the intake rates of CH4 and CO2 were 15 mL / min respectively, and the dosage of each CH4-CO2 reforming catalyst was 0.05 g. The conversion rate of the reforming reaction of CH4 and CO2 catalyzed by each CH4-CO2 reforming catalyst was measured. The results are shown in Tables 1 and 2.
[0050] Table 1 Conversion rate of CH4 in the reaction gas of each catalyst catalytic test at different reaction temperatures
[0051]
[0052] Table 2 Conversion rate of CO2 in the reaction gas of each catalyst catalytic test at different reaction temperatures
[0053]
[0054] It can be seen from Tables 1 and 2 that the selection of different active metal salts and carbon-containing precursors has a certain influence on the catalytic performance of the catalyst. The CH4-CO2 reforming catalyst prepared with cobalt nitrate and polyacrylonitrile (PAN) as the active metal salt and carbon-containing precursor respectively has the best catalytic performance. However, the size of the applied voltage set during the electrospinning process has no obvious difference in the catalytic performance of the CH4-CO2 reforming catalyst. In addition, the test results also show that the CH4-CO2 reforming catalyst prepared by the present invention, although the amount of CH4-CO2 reforming catalyst used in the catalytic reaction is small, the conversion rates of CH4 and CO2 are relatively high.
[0055] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. Application of a carbon fiber-based CH4-CO2 reforming catalyst in a CH4-CO2 reforming reaction, characterized in that: Active metal-carbon composite nanofibers are prepared by electrospinning, and the active metal-carbon composite nanofibers are calcined in an inert atmosphere to obtain a carbon fiber-based CH4-CO2 reforming catalyst; The specific steps include: S1: dispersing the active metal salt in an ethanol solution to obtain a mixed dispersion; S2: adding a carbon-containing precursor to the mixed dispersion, stirring and mixing until the carbon-containing precursor is completely dispersed and uniformly dispersed, thereby obtaining an electrospinning material; S3: preparing active metal-carbon composite nanofibers from the electrospinning material by an electrospinning method; S4: placing the active metal-carbon composite nanofibers in a tubular furnace, introducing an inert gas for calcination, and naturally cooling after the calcination to obtain a carbon fiber-based CH4-CO2 reforming catalyst; In step S1, the active metal salt is any one of cobalt nitrate, cobalt acetate or cobalt acetylacetonate, or a mixture of two or more thereof; the ethanol solution is a mixture of anhydrous ethanol and water in a volume ratio of 5:5 to 7:3; In step S2, the carbon-containing precursor is any one of polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyurethane (PU), polyvinyl pyrrolidone (PVP) or polymethyl methacrylate (PMMA), or a mixture of two or more thereof; In step S3, during the electrospinning process, the electrospinning material is placed in a syringe of an electrospinning device, and the flow rate of the syringe pump is 10 to 15 μL / min; the applied voltage is set to 13 to 19 kV, and the receiving distance is 15 to 20 cm; the active metal-carbon composite nanofibers are received through aluminum foil; In step S4, during roasting, the tube furnace is first heated to the roasting temperature at a heating rate of 5°C / min, and then roasting is performed at the roasting temperature; the roasting temperature is 700-800°C, and the roasting time is 3-5h.
2. The use of a carbon fiber-based CH4-CO2 reforming catalyst in a CH4-CO2 reforming reaction according to claim 1, characterized in that: In step S1, in the mixed dispersion, the ratio between the mass of the active metal salt and the volume of the ethanol solution is 0.04-0.08 g / mL.
3. The use of a carbon fiber-based CH4-CO2 reforming catalyst in a CH4-CO2 reforming reaction according to claim 1, characterized in that: In step S2, the molar ratio of the active metal in the mixed dispersion to the carbon atoms in the carbon-containing precursor is 1:(5-15).
4. The use of a carbon fiber-based CH4-CO2 reforming catalyst in a CH4-CO2 reforming reaction according to claim 1, characterized in that: In step S3, the diameter of the active metal-carbon composite nanofibers is 200-400 nm.
Citation Information
Patent Citations
Carbon nanofiber catalysts using nanofiber including low cost transition metal for fuel cells and manufacturing method thereof
WO2012074160A1